Correlation of legumes' glycemic index with its digestibility: A review / Nurul Diyanah Mohd Tahar and Nur Rabiatul Adawiah Mohammad Noor - Mohd Tahar, Nurul Diyanah; Mohammad Noor, Nur Rabiatul Adawiah (2021)
Legumes are a carbohydrate-containing food that has become a staple food for some individuals due to their ability to give people extended satiety. This is due to the slow digestion of foods for glucose utilization, implying a low glycemic index (GI). However, a sedentary lifestyle might prefer to consume high amounts of a carbohydrate-rich food such as white rice or white bread, commonly known as high GI foods. As a result, blood sugar levels rise rapidly, causing people to feel fuller for a short period, driving them to obesity or type II diabetes. This study includes a discussion of major findings related to the intrinsic and extrinsic factors that influence the starch digestibility in legumes. The intrinsic factors are the amylose-amylopectin ratio, starch structure, dietary fibre, and phytic acid. At the same time, the extrinsic factors are the rigid cell wall, the cooking methods, and the retrogradation process. These factors were evaluated by using the in-vitro or in-vivo method. According to a recent study, legumes with high amylose: amylopectin ratio had a higher tendency to retrograde during gelatinization, resulting in a crystal structure resistant to digesting enzymes. Legumes have robust cell walls that make it difficult for the enzyme to penetrate the starch. Thus, the digestion process took longer. Daily food intake of legumes could improve better health and guard against type-II diabetes, lower blood pressure, and even cholesterol. The food manufacturing industry should be considered in the extensive production of legume-based food products.